Taxonomy of organic-walled microfossils from the Sete Lagoas Formation, Brazil : biostratigraphy and paleobiogeography of Gondwana during Ediacaran - Denezine, Matheus (2022)
Tese (doutorado) — Universidade de Brasília, Instituto de Geociências, Programa de Pós-Graduação em Geologia, 2022.